Formulation of alternative media for fungal growth and its application as agarwood-inducing agent in Aquilaria trees - M. R., Sheriza; Z., Rozihawati; W. A., Wan Muhammad Azrul; Noor Baity; A. H., Hazandy; A., Mohd Farid; S., Zaiton (Forest Research Institute Malaysia,Institut Penyelidikan Perhutanan Malaysia, 2022)
This study investigated the growth performance of Fusarium proliferatum isolated from agarwood, on different types of plated media prepared with liquid broth extracts of locally available agricultural products. The potential of F. proliferatum in selected media to induce agarwood formation in Aquilaria trees was also assessed. A total of 27 media formulations were evaluated as alternative media to potato dextrose agar (PDA) for F. proliferatum. The effects of culture media on the diameter growth of fungal mycelium were significant (F = 6.70, df = 26, p < 0.01). The best growth was recorded on 50% soybean followed by PDA and 70% kidney bean with mean mycelium diameters of 7.00 ± 0.00, 6.63 ± 0.83 and 6.50 ± 0.06 cm respectively. In the field trial, F. proliferatum in all three media successfully induced agarwood formation on A. malaccensis and A. crassna with significant discoloration zones compared with the uninoculated control trees (p ≤ 0.05) after five months. Fifty percent soybean in combination with F. proliferatum induced the largest discoloration zone, indicating potential as a cheaper and more accessible alternative to PDA. These results suggest that the combination of a chemical inducer in the form of a liquid media formulation and a biological inducer, in this case, an endophytic fungus could successfully induce agarwood formation in Aquilaria trees.